Estrategias aplicadas en redes sociales durante la campaña presidencial del ecuador, en la segunda vuelta 2021. - Sanmartín Chimbo, Diana Lisbeth (2025)
This research analyzes the digital strategies employed on social media during the second round of the 2021 presidential elections in Ecuador, highlighting the use of platforms such as Facebook, Twitter, Instagram, and TikTok. In a context marked by the COVID-19 pandemic, these networks became essential tools for political communication, enabling direct interaction between candidates and voters, overcoming the limitations on physical contact imposed by the health crisis. The study focused on the strategies of Andrés Arauz and Guillermo Lasso, analyzing 120 relevant posts, official documents, and digital metrics from Meta Business Suite and Twitter Analytics. The results show that TikTok emerged as the platform with the highest relative reach, generating significantly higher interactions thanks to audiovisual and emotional content. Additionally, posts with a positive tone demonstrated a greater ability to favorably influence voter perception. On the other hand, strategic differences were identified: while Lasso prioritized a more emotional approach on TikTok and Instagram, Arauz focused on economic proposals distributed evenly across several platforms. Despite this, both candidates faced ethical and legal challenges, such as misinformation and the lack of regulation in the use of social media, underscoring the need for a regulatory framework to ensure more transparent electoral processes. In conclusion, digital strategies played a decisive role in the 2021 elections, transforming social media into a key channel for electoral mobilization and shaping public opinion. This study highlights the importance of adopting ethical and transparent practices in the use of these platforms and promoting their regulation in future democratic processes.